Oscillation Theorems Concerning Damped Nonlinear Differential Equations Of Second Order (Faculty of Education Scientific Journal, 2023)
In this paper, some oscillation criteria for solutions of second order damped nonlinear differential equations of the formare obtained. Our results improve and extend some existing results in the literature. Some examples are given with its numerical solutions, which are computed using Runge Kutta method of fourth order to illustrate our results.